Routledge Handbook of Violent Extremism and Resilience - McNeil-Willson, Richard; Triandafyllidou, Anna (Routledge International Handbooks, 2023)
At a time of great global uncertainty and instability, communities face fracturing from the increasing influence of extremist movements hostile to democratic and multicultural norms. Europe and the West have grown increasingly polarised in recent years, beset with financial crises, political instability, the rise of malicious actors and irregular violence, and new forms of media and social media. These factors have enabled the spread of new forms of extremism and suggest a growing need for a response sensitive to inequalities and divisions in wider society - a task made even more urgent by the COVID-19 pandemic. The Routledge Handbook of Violent Extremism and Resilience brings together research conducted throughout Europe and the world, to analyse various articulations of violent extremism and consider the impact that such groups and networks have had on the wellbeing of communities and societies. It examines different theories, factors and national case studies of extremism, polarisation and societal fragmentation, drilling deep into national examples to map trends across Europe, North America and Australasia, to provide regional and state-level comparative analysis. It also offers a thorough exploration of resilience - a recent addition to counter-extremism policy and practice - to consider how it has come to play this increasingly central role in Preventing and Countering Violent Extremism (P/CVE), the limitations and opportunities of such approaches, and how it could be shared, developed, problematised and deployed in response to violence and polarisation. The Handbook details new trends in both violent extremism and counter-extremism response, within this increasingly fractured global context. It critically explores the latest theories of community violence, extremism, polarisation and resilience, mapping them across case study countries. In doing so, it presents new findings for students, researchers, practitioners and policymakers seeking to understand these new patterns of polarisation and extremism and develop community-driven responses.